A desvalorização do corpo na infância: análise de uma experiência no estágio supervisionado em educação infantil - Ginna, Bárbara (Universidade Federal de São Carlos, 2015)
The object of this study is the devaluation of the child's body at school. The study aimed to investigate the historical reasons for the repression of movement in school education, the reasons why domestication practices are accepted by education professionals as being effective and the consequences of the oppression of the body in the formation of the child as a subject. The text is divided into three chapters. Chapter I consists of a historical survey, from the perspective of Michel Foucault, on the issue of repression of bodies, aiming to understand how it happened historically and what is its connection and possible articulation with the education of subjects at school. The second chapter presents the methodological paths followed in the work, which were the bibliographical survey, observation in the context of a supervised internship in Early Childhood Education, data collection and field diary records, in addition to describing the situation of the internship performed, the researched context and its subjects. Chapter III contains data analysis, which consists of efforts to intertwine field data with the theoretical foundation and with the experiences lived by the author in practice.
The devaluation of the body in childhood: analysis of an experience in supervised internship in early childhood education
Keywords: Corpo; Body; Infância; Childhood; Educação infantil; Early childhood education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO